Effects of grapeVitis viniferaseed oil supplementation on growth, survival, fatty acid profiles, antioxidant contents and blood parameters in rainbow troutOncorhynchus mykiss - Arslan, Gökhan; Sönmez, Adem Yavuz; Yank, Telat (Wiley, 2018)
In this study, effects of grape Vitis vinifera seed oil supplementation (0, 250 mg, 500 mg, 1,000 mg/kg feed) for 60 days on rainbow trout Oncorhynchus mykiss juveniles were investigated. The average final fish weights were not different between the control group and 500 mg/kg feed group (p > .05), but 250 mg/kg feed group were lower than those of the control group, and 1,000 mg/kg feed group were higher than those of the control group. Although the SFA, MUFA and n3 ratios of the control group were higher than that of the other groups, no statistical difference was found. The highest fatty acids in the fish were palmitic acid C 16: 0 in the SFA group and C 18: 1n‐9 and docosahexaenoic acid C 22: 6n‐3 in the PUFA group. The EPA ratio was significantly increased in all groups compared with the control group. The DHA ratio was significantly higher in the control group than in the experimental groups, and there was no difference between the experimental groups. Urea were significantly lower in the 250 mg/kg feed group. Total protein and aspartate aminotransferase were significantly increased in the 1,000 mg/kg feed group. Only the 1,000 mg/kg feed group showed an increase in antioxidant activities, and this concentration also yielded positive results in terms of growth performance, survival rates, fatty acid composition and antioxidant enzyme activities in rainbow trout juvenile and can be used as a natural feed additive.
Keywords: 13. Climate action; 14. Life underwater; 3. Good health